2018
DOI: 10.1002/jmor.20815
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal histology of box jellyfish (Cnidaria: Cubozoa) reveals variation between internal fertilizing species Alatina alata (Alatinidae) and Copula sivickisi (Tripedaliidae)

Abstract: Cubozoans (box jellyfish) are gonochoristic cnidarians with distinct reproductive strategies. This comparative histological study examines the gonad organization of Alatina alata and Copula sivickisi, two box jellyfish species that exhibit different modes of internal fertilization. A. alata reproduces via spermcasting aggregations while C. sivickisi reproduces via copulation; in both cases, internal fertilization occurs in the gastrovascular cavity. Herein, we provide the first histological description of subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…This is supported by our finding that one of the examined females had a spermatozeugma attached to a hemi‐gonad (Figure a, insert). It has also been suggested that the isorhizas are used to anchor the spermatozeugmata to the female tentacles during mating (Garcia‐Rodriguez et al, ), but these hypotheses are not mutually exclusive. Only ripe sperm cells are included in the spermatozeugmata leaving the immature sperm behind in the hemi‐gonad and each hemi‐gonads can thus form several spermatozeugmata over time (present work, Straehler‐Pohl et al, ; Garcia‐Rodriguez et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is supported by our finding that one of the examined females had a spermatozeugma attached to a hemi‐gonad (Figure a, insert). It has also been suggested that the isorhizas are used to anchor the spermatozeugmata to the female tentacles during mating (Garcia‐Rodriguez et al, ), but these hypotheses are not mutually exclusive. Only ripe sperm cells are included in the spermatozeugmata leaving the immature sperm behind in the hemi‐gonad and each hemi‐gonads can thus form several spermatozeugmata over time (present work, Straehler‐Pohl et al, ; Garcia‐Rodriguez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the isorhizas are used to anchor the spermatozeugmata to the female tentacles during mating (Garcia‐Rodriguez et al, ), but these hypotheses are not mutually exclusive. Only ripe sperm cells are included in the spermatozeugmata leaving the immature sperm behind in the hemi‐gonad and each hemi‐gonads can thus form several spermatozeugmata over time (present work, Straehler‐Pohl et al, ; Garcia‐Rodriguez et al, ). This strongly suggests that even though the female of T. cystophora only mates once (Werner, ), the male can have multiple matings like seen for C. sivickisi (Lewis & Long, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations